(untitled) (Damascus University Journal for engineering sciences, 2021)
During the evaluation of laboratory tests; results where the more accurate the results, the more effective the treatment. There are several ways to confirm this accuracy; including statistical methods based on the study of basic statistical parameters, which often contribute to inaccuracy because the technician is not sufficiently qualified, it needs to be recalibrated, the reagents are ineffective, the absence or incorrect blanc. The study of the causes of errors in diagnosing the results of clinical laboratory analyses and the lessening of these errors increase the quality of the results of laboratory tests. The main reasons for measurement errors are the absence of calibration solution and thoughtful use of standard solutions and the design of standard curves. We will explain the large effect of standard solutions on the accuracy of the results and therefore on the quality of the results of laboratory analysis because the measured values of a given analyses are compared with the values and standard curves stored in the measuring device.